A Review on Intellectual Property Rights of Biosafety (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The interconnection between intellectual property rights (IPRs) and biosafety has become increasingly significant in the era of biotechnology and genetic modification. While IPRs aim to promote innovation and economic development by protecting new biotechnological inventions, they also raise complex ethical, environmental, and social challenges. This review explores the delicate balance between the protection of genetic innovations through patents and the preservation of biodiversity and environmental safety. It examines global & Indian legal frameworks, including the TRIPS Agreement, the Cartagena Protocol on Biosafety, and national legislations such as the Biological Diversity Act (2002), the Patent Act (2005), and the Seeds Bill (2004). The study highlights how biosafety regulations are essential in managing the potential risks posed by GMOs to human health and ecosystems. Furthermore, it discusses the need for aligning intellectual property regimes with sustainable development goals, emphasizing liability, public participation, and the precautionary principle. The review concludes that an integrated approach combining biosafety governance and intellectual property protection can promote responsible innovation while safeguarding environmental and social interests.